Effect of Gurney Flap on The Flow Separation Phenomenon on The Rear Wing Airfoil of Racing Car - Kurniawan, Dondi; Yoanita, Yulia Venti; Pinindriya , Sinung Tirtha; Kumolosari, Eli; Prabowo, Angga Darma (Open Science and Technology, 2025)
Background: A racing car must be able to run at high speeds. To achieve this goal, vehicle aerodynamic modifications are often carried out, one of which is adding a gurney flap (GF). The GF on a racing car function to delay the flow separation, increase the downforce value, and reduce the drag force.Aims & Methods: In this study, observations of the influence of GF were carried out by numerical simulation using Solidworks 2025 by varying the speed of 250, 320, and 400 km/h at an angle of attack of 0°, with and without GF. The aim is to obtain information on the influence of these variations on the flow separation phenomenon on the rear wing airfoil.Result: The results showed that the addition of GF caused a delay in flow separation and a decrease in wake/vortex behind the airfoil. The impact was that the drag force increased at low speeds (39.97% at 250 km/h) but showed a decrease at medium and high speeds, namely -7.91% at 320 km/h and -2.31% at 400 km/h.